2011
DOI: 10.1007/s10664-011-9173-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating defect prediction approaches: a benchmark and an extensive comparison

Abstract: Reliably predicting software defects is one of the holy grails of software engineering. Researchers have devised and implemented a plethora of defect/bug prediction approaches varying in terms of accuracy, complexity and the input data they require. However, the absence of an established benchmark makes it hard, if not impossible, to compare approaches. We present a benchmark for defect prediction, in the form of a publicly available dataset consisting of several software systems, and provide an extensive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
335
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(344 citation statements)
references
References 68 publications
8
335
1
Order By: Relevance
“…Surprisingly, the results about precision in Table III are, on average, higher than those in Table II, implying that CPDP achieves better performance than WPDP in this example. This finding is different from the results of many prior studies [3,9]. Similarly, Figure 3 shows that in the scenario of CPDP DTR is also the best estimator when considering precision.…”
Section: A Answer To Rq1contrasting
confidence: 85%
See 1 more Smart Citation
“…Surprisingly, the results about precision in Table III are, on average, higher than those in Table II, implying that CPDP achieves better performance than WPDP in this example. This finding is different from the results of many prior studies [3,9]. Similarly, Figure 3 shows that in the scenario of CPDP DTR is also the best estimator when considering precision.…”
Section: A Answer To Rq1contrasting
confidence: 85%
“…Interestingly, several recent studies with respect to software defect classification [3,9,10] have found that simple classifiers, e.g., Naïve Bayes and Logistic Regression, were able to perform well in both within-project and cross-project scenarios, though those complex ones always achieved high precision. As we know, newly created or unpopular software projects have little historical data available to train any classifiers, which is very similar to the typical problem cold start in recommender systems [11].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of our research is to empirically study performance of various classifiers for fault prediction on the data sets provided by Marco D'Ambros [45].…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
“…http://sourcerer.ics.uci.edu/ • Ultimate Debian Database (UDD) [11] http://udd.debian.org/ • Bug Prediction Dataset (BPD) [12], [13]:…”
Section: Research Datasetsmentioning
confidence: 99%